Exploring Group Composition among Young, Urban Women of Color in Prenatal Care: Implications for Satisfaction, Engagement, and Group Attendance. - Earnshaw, Valerie A; Rosenthal, Lisa; Cunningham, Shayna D; Kershaw, Trace; Lewis, Jessica; Rising, Sharon Schindler; Stasko, Emily; Tobin, Jonathan; Ickovics, Jeannette R (Women's health issues : official publication of the Jacobs Institute of Women's Health, 2015)
Group models of prenatal care continue to grow in popularity. However, little is known about how group composition (similarity or diversity between members of groups) relates to care-related outcomes. The current investigation aimed to explore associations between prenatal care group composition with patient satisfaction, engagement, and group attendance among young, urban women of color.